Corporate social responsibility disclosure and firms' performance in Mediterranean countries: a stakeholders' perspective. Issue 3 (15th April 2020) - Buallay, Amina; Kukreja, Gagan; Aldhaen, Esra; Al Mubarak, Muneer; Hamdan, Allam Mohammed
Abstract : Purpose: The purpose of this study is to investigate the relationship between corporate social responsibility (CSR) disclosure and firms' operational, financial and market performance (measured in the form of return on assets (ROA), return on equity (ROE) and Tobin's Q (TQ), respectively) in the Mediterranean countries from a stakeholder perspective. Design/methodology/approach: Research is quantitative in nature, based on a cross-sectional and time-series analysis of 203 firms listed in six Mediterranean countries for 10 years from 2008 to 2017, with 1, 689 observations. The theoretical model is built on a stakeholder theory. The practical model is built on the independent variable (CSR) and the dependent variables ROA, ROE and TQ. Findings: The findings deduced from the empirical results indicated that CSR disclosure negatively affects operational and market performance but does not affect financial performance. Practical implications: Studying the relationship between CSR disclosure and firms' operational, financial and market performance, with the consideration of variations, can bring many benefits internally by being more conscious of important activities that should be undertaken and externally by detecting what regulators and other stakeholders want for better sustainable development. Originality/value: This research adds value to the existing limited literature of CSR disclosure on firm's performance in the Mediterranean countries, and it gives tips of advice for firms to manage CSR disclosure wisely.